Ar-Rasāil Ad-Da’wiyyah fi Riwāyati Kemi : Cinta Kebebasan Yang Tersesat Karya Adian Husaini - Faqih Usman; Hadil Ismail Hasan (Mauriduna: Journal of Islamic Studies, 2022)
All this time, Da'wah has been known identically for oral preaching. Through the development of da'wah media with modern technology, it requires all parties, especially da'wah activists to always be creative and innovative in utilizing the technology intended for the benefit of mankind. Same as the novel which is now used as a tool for delivering da'wah. This research focused on what da'wah messages are contained inside the Kemi : Cinta Kebebasan Yang Tersesat novel by Adian Husaini and identified the da'wah messages contained inside the Kemi : Cinta Kebebasan Yang Tersesat novel by Adian Husaini. To achieve these goals, the researcher carries out a qualitative descriptive analysis approach by looking at the paragraphs and conversations containing the da'wah messages inside Adian Husaini's KEMI Novel, collecting, analyzing, classifying, presenting, and concluding. Research shows that it contains the dakwah akidah, the syari'ah, and moral. The result of this research there are 5 da'wah messages of theology regarding faith in Allah, 3 da'wah messages of morality, which are relying upon god, being grateful, and having good relations with fellow human beings. There are 3 dakwah messages of shari'ah, among them is the obligation to pray, repent and ask Allah for help. Dakwah selama ini identik dengan ceramah melalui lisan. Melalui perkembangan media dakwah dengan teknologi modern ini menuntut semua pihak, khususnya aktivis dakwah untuk senantiasa kreatif dan inovatif dalam memanfaatkan teknologi yang dimaksud guna kemaslahatan umat manusia. Seperti halnya novel, yang pada zaman sekarang yang dijadikan alat dalam menyampaikan dakwah. Fokus penelitian ini adalah pesan dakwah yang terkandung di novel Kemi : Cinta Kebebasan Yang Tersesat karya Adian Husaini dan mengidentifikasi pesan-pesan dakwah yang terkandung di dalamnya. Untuk mencapai tujuan-tujuan tersebut, peneliti menggunakan pendekatan kualitatif analisis deskriptif dengan mencermati paragraf dan percakapan yang mengandung pesan dakwah dalam tersebut, dengan mengumpulkan, menganalisis, mengklasifikasikan, menyajikan dan menyimpulkan. Hasil penelitian menunjukkan bahwa novel mengandung pesan dakwah berupa pesan akidah, syari’ah, dan akhlak. Penelitian ini menghasilkan bahwa terdapat 5 pesan dakwah aqidah mengenai iman kepada Allah. 3 pesan dakwah akhlak yaitu tentang bertawakkal, bersyukur dan berhubungan baik dengan sesama manusia. Terdapat 3 pesan dakwah syari’ah yaitu tentang kewajiban sholat, taubat dan meminta pertolongan kepada Allah.